Work Motivation of The Regional Financial and Revenue Management Agency in Soppeng Regency - Muh. Yusuf; Muh. Akmal Ibrahim; Badu Ahmad (Enrichment : Journal of Management, 2022)
The purpose of this study was to analyze the ranking of motivation, using a survey research method with a quantitative approach. The method of collecting data is through a questionnaire containing structured statements addressed to respondents. The total population is 98 people with an error rate of 5% and the number of samples is 80 people. The results of data analysis show that there is a ranking of work motivation from two motivational factors, namely intrinsic factors and extrinsic factors. Intrinsic factors include responsibility, the work itself, and opportunities for growth, while extrinsic factors include salary, working conditions, and interpersonal relationships.